Social Interaction of K-Pop Fans Students of Kpi-A Fdk UINSU 2021 on Tiktok According to The Perspective of Islamic Communication - khairunisa harani harahap; Tengku Walisyah (UIN Fatmawati Sukarno Bengkulu, 2025)
The K-Pop phenomenon has crossed 41% of geographical and language boundaries, thereby strengthening cultural relations between Indonesia and South Korea.Fans actively participate in fan meetings and concerts, which are then supported by the internet as the main means of spreading the “Korean Wave.” Streaming platforms such as TikTok, YouTube, Netflix, Twitter, Instagram and Viu facilitate direct legal access between fans and idols to their favorite K-Drama and K-Pop, thus strengthening group cohesion and identity. In accordance with the theory of Group Dynamics by Kurt Lewin. Especially for K-Pop fans among female students of the Islamic Communication and Broadcasting Study Program (KPI) Faculty of Da'wah and Communication (FDK) State Islamic University of North Sumatra (UINSU) class of 2021. How do these female students carry out their social interactions on TikTok as K-Pop fans without neglecting Islamic values? This approach is important considering the challenges faced by the younger generation of Muslims in maintaining a balance between modern life and religious principles that guide their lives. The research method used in this writing is qualitative from the field research type. Data collection through observation, interviews, and documentation studies. The results of the study found that the social interaction of K-pop fans of KPI-A FDK UIN SU students on TikTok has two sides, namely positive in building community and support, but also prone to conflict. From the perspective of Islamic communication, this interaction does not fully reflect Islamic values, but has the potential to be more positive with user awareness of communication ethics. TikTok can also be an effective means of spreading Islamic messages if used wisely by the K-pop fan community.